The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Economic “Activity-Silent” Synaptic Mechanisms of Working Memory - Xiao Lin; Ying Han; Peng Li; Le Shi; Lin Lu (Neuroscience Bulletin, 2017)

Morphological characteristics and DNA barcoding of Pampus echinogaster (Basilewsky, 1855) - Yuan Li; Yan Zhang; Tianxiang Gao; Zhiqiang Han; Longshan Lin; Xiumei Zhang (Acta Oceanologica Sinica, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Development of a stable Japanese encephalitis virus replicon cell line for antiviral screening - Qiu-Yan Zhang; Xiao-Dan Li; Si-Qing Liu; Cheng-Lin Deng; Bo Zhang; Han-Qing Ye (Archives of Virology, 2017)

Microbial population structure in near-ground aerosols during fog-haze days in northern China - Yunping Han; Mengzhu Zhang; Lin Li; Junxin Liu (Air Quality, Atmosphere & Health, 2017)

Interannual variation in methane emissions from tropical wetlands triggered by repeated El Niño Southern Oscillation - Qiuan Zhu; Changhui Peng; Philippe Ciais; Hong Jiang; Jinxun Liu; Philippe Bousquet; Shiqin Li; Jie Chang; Xiuqin Fang; Xiaolu Zhou; Huai Chen; Shirong Liu; et al. (Global Change Biology, 2017)
Methane (CH 4 ) emissions from tropical wetlands contribute 60%–80% of global natural wetland CH 4 emissions. Decreased wetland CH 4 emissions can act as a negative feedback mechanism for future climate warming and vice versa. The impact of the El Niño–Southern Oscillation (ENSO) on CH 4 emissions from wetlands remains poorly quantified at both regional and global scales, and El Niño events are expected to become more severe based on climate models’ projections. We use a process‐based model of global wetland CH 4 emissions to investigate the impacts of the ENSO on CH 4 emissions in tropical wetlands for the period from 1950 to 2012. The results show that CH 4 emissions from tropical wetlands respond strongly to repeated ENSO events, with negative anomalies occurring during El Niño periods and with positive anomalies occurring during La Niña periods. An approximately 8‐month time lag was detected between tropical wetland CH 4 emissions and ENSO events, which was caused by the combined time lag effects of ENSO events on precipitation and temperature over tropical wetlands. The ENSO can explain 49% of interannual variations for tropical wetland CH 4 emissions. Furthermore, relative to neutral years, changes in temperature have much stronger effects on tropical wetland CH 4 emissions than the changes in precipitation during ENSO periods. The occurrence of several El Niño events contributed to a lower decadal mean growth rate in atmospheric CH 4 concentrations throughout the 1980s and 1990s and to stable atmospheric CH 4 concentrations from 1999 to 2006, resulting in negative feedback to global warming.

Design, synthesis, antitumor evaluation, 3D-QSAR and molecular docking studies of novel 4-aminoacridone compounds - Lin Tian; Chang J. Feng; Tong X. Li; Zhao Li; Wei H. Yang; Xiang E. Han (Medicinal Chemistry Research, 2017)

The effects of different irrigation regimes on nitrous oxide emissions and influencing factors in greenhouse tomato fields - Bing Han; Xuhong Ye; Wen Li; Xichao Zhang; Yulong Zhang; Xiangui Lin; Hongtao Zou (Journal of Soils and Sediments, 2017)

Postural Stability Assessment in Patients with Mild Traumatic Brain Injury Complaining of Dizziness - Kai-Yun Chen; Shih-Wei Huang; Yen-Nung Lin; Chun-De Liao; Wen-Hsuan Hou; Tsan-Hon Liou; Yung-Hsiao Chiang; Shin-Han Tsai; Wen-Ta Chiu; Wei-Chun Hsu; Li-Fong Lin (Journal of Medical and Biological Engineering, 2017)

Two new diketopiperazines from the tin mine tailings-derived fungus Schizophyllum commune YIM DT 10058 - Wei-Xun Chunyu; Zhang-Gui Ding; Jiang-Yuan Zhao; Yong-Xia Wang; Xiu-Lin Han; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2017)

Puerarin may protect against Schwann cell damage induced by glucose fluctuation - Bing Xue; Lin Wang; Zhe Zhang; Rui Wang; Xin-xin Xia; Ping-ping Han; Li-jun Cao; Yong-hui Liu; Lian-qing Sun (Journal of Natural Medicines, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

EGCG protects against homocysteine-induced human umbilical vein endothelial cells apoptosis by modulating mitochondrial-dependent apoptotic signaling and PI3K/Akt/eNOS signaling pathways - Shumin Liu; Zhengwu Sun; Peng Chu; Hailong Li; Anil Ahsan; Ziru Zhou; Zonghui Zhang; Bin Sun; Jingjun Wu; Yalin Xi; Guozhu Han; Yuan Lin; et al. (Apoptosis, 2017)

Global land surface climate analysis based on the calculation of a modified Bowen ratio - Bo Han; Shihua Lü; Ruiqing Li; Xin Wang; Lin Zhao; Cailing Zhao; Danyun Wang; Xianhong Meng (Advances in Atmospheric Sciences, 2017)

Mechanistic and therapeutic perspectives for cardiac arrhythmias: beyond ion channels - Yufei Wu; Jun Li; Liang Xu; Li Lin; Yi-Han Chen (Science China Life Sciences, 2017)

Follistatin-like protein 1 suppressed pro-inflammatory cytokines expression during neuroinflammation induced by lipopolysaccharide - Kai-Yuan Cheng; Yi Liu; Ying-Guang Han; Jing-Kun Li; Jia-Lin Jia; Bin Chen; Zhi-Xiao Yao; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2017)

Enterovirga rhinocerotis gen. nov., sp. nov., isolated from Rhinoceros unicornis faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Hui Lei; Yi Jiang; Li Han; Xue-Shi Huang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2017)

Retraction Note to: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Complete chloroplast genome sequence of Chinese larch (Larix potaninii var. chinensis), an endangered conifer endemic to China - Kai Han; Jianfang Li; Shuyun Zeng; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Characterization of the complete chloroplast genome of Platycarya strobilacea (Juglandaceae) - Jing Yan; Kai Han; Shuyun Zeng; Peng Zhao; Keith Woeste; Jianfang Li; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Wind and salt spray alter tree shape and dry mass density in Casuarina equisetifolia L. - Yongming Lin; Jian Li; Jonathan D. Bakker; Han Lin; Can Chen; Wei Hong; Loretta Fisher; Chengzhen Wu; Tao Hong; Haojun Deng; Guangshuai Zhang; Kun Du (Trees, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Salidroside accelerates fracture healing through cell-autonomous and non-autonomous effects on osteoblasts - Xiao Qin Guo; Lin Qi; Jing Yang; Yue Wang; Chuan Wang; Zong Min Li; Ling Li; Ye Qu; Dan Wang; Ze Min Han (Cell and Tissue Research, 2017)

Chemical composition and antioxidant activities of essential oils from different parts of the oregano - Fei Han; Guang-qiang Ma; Ming Yang; Li Yan; Wei Xiong; Ji-cheng Shu; Zhi-dong Zhao; Han-lin Xu (Journal of Zhejiang University-SCIENCE B, 2017)

Detection of genotoxic effects of drinking water disinfection by-products using Vicia faba bioassay - Yu Hu; Li Tan; Shao-Hui Zhang; Yu-Ting Zuo; Xue Han; Na Liu; Wen-Qing Lu; Ai-Lin Liu (Environmental Science and Pollution Research, 2017)

Inoculation with endophytic Bacillus megaterium H3 increases Cd phytostabilization and alleviates Cd toxicity to hybrid pennisetum in Cd-contaminated aquatic environments - Ya Li; Hui Han; Lin Yan He; Qi Wang; Xia Fang Sheng (Environmental Science and Pollution Research, 2017)

Effect of LA on the Growth and Development of the Main Organs in Female Mice - Xiuyuan He; Feng Lin; Yongtao Li; Yuxia Chen; Jing Li; Linlin Guo; Xuelei Han; Huan Song (Biological Trace Element Research, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

Oceanic currents drove population genetic connectivity of the brown alga Sargassum thunbergii in the north‐west Pacific - Jing‐Jing Li; Zi‐Min Hu; Xu Gao; Zhong‐Min Sun; Han‐Gil Choi; De‐Lin Duan; Hikaru Endo (Journal of Biogeography, 2017)
Aim Oceanic currents are among the most pervasive hydrodynamic features in shaping community dynamics, population connectivity and phylogeographical structure of intertidal species. Here, we test whether population structure and biogeographical gradients of genetic diversity in the brown alga Sargassum thunbergii are correlated with oceanic currents in the north‐west Pacific ( NWP ). Location North‐west Pacific (25.07°N–43.36°N). Methods Nuclear internal transcribed spacer‐2 and mitochondrial cox 3 sequences were obtained from 835 and 810 individuals of S. thunbergii respectively. Parsimony networks and phylogenetic trees (maximum parsimony and Bayesian inference) were constructed to evaluate phylogeographical structure. Pairwise F ST estimates and analyses of molecular variance ( AMOVA ) at various hierarchical levels (latitude, longitude, marine provinces, biogeographical basins and zoogeographical zones) were conducted to elucidate population genetic differentiation. migrate software was used to estimate the number of migrants between adjacent populations. Results Several lines of evidence indicate that S. thunbergii is characterized by shallow population structure. Geographical distances do not correlate with population pairwise genetic differentiations. The corridor/stepping‐stone model‐based coalescent analyses reveal high levels of asymmetric gene flow among S. thunbergii populations, with the numbers of migrants largely corresponding to the directions of oceanic current systems in the NWP . Genetic signatures also indicate that Jeju Island, Korea might act as a transition zone for dispersal of S. thunbergii in the NWP driven by the Kuroshio Current, thus facilitating subsequent transportation northward into the Sea of Japan and the Yellow‐Bohai Sea. Main conclusions Population genetic homogeneity in S. thunbergii was mainly structured by oceanic currents rather than palaeoclimatic events. Our study illustrates an important phylogeographical case of how coastal hydrodynamic factors contributed to population connectivity and geographical shifts of genetic diversity for marine organisms without a pelagic stage.